Using the properties of operations and rules for multiplying and dividing, we can solve the expression:
(-3) ÷ (34) × (27) × (-516) ÷ (57)
First, we can perform the division of -3 ÷ 34 which equals approximately -0.0882.
Next, we multiply this result by 27: -0.0882 × 27 ≈ -2.3814.
Then, we multiply this by -516: -2.3814 × (-516) = 1227.164.
Finally, we divide this by 57: 1227.164 ÷ 57 ≈ 21.543.
Therefore, (-3) ÷ (34) × (27) × (-516) ÷ (57) is approximately equal to 21.543.
Use the properties of operations and rules for multiplying and dividing to solve:
(−3)÷(34)×(27)×(−516)÷(57)
(1 point)
40 answers
ahem incorrect sir
Apologies for the error in my previous response. Let's solve the expression correctly:
(-3) ÷ (34) × (27) × (-516) ÷ (57)
To solve this expression, we'll follow the order of operations, which is parentheses, multiplication/division (from left to right), and finally, addition/subtraction (from left to right).
First, let's calculate the division -3 ÷ 34, which is approximately -0.0882.
Next, we can multiply -0.0882 by 27: -0.0882 × 27 = -2.3826.
Then, we multiply -2.3826 by -516: -2.3826 × (-516) = 1229.5536.
Finally, we divide 1229.5536 by 57: 1229.5536 ÷ 57 ≈ 21.579.
Therefore, (-3) ÷ (34) × (27) × (-516) ÷ (57) is approximately equal to 21.579.
(-3) ÷ (34) × (27) × (-516) ÷ (57)
To solve this expression, we'll follow the order of operations, which is parentheses, multiplication/division (from left to right), and finally, addition/subtraction (from left to right).
First, let's calculate the division -3 ÷ 34, which is approximately -0.0882.
Next, we can multiply -0.0882 by 27: -0.0882 × 27 = -2.3826.
Then, we multiply -2.3826 by -516: -2.3826 × (-516) = 1229.5536.
Finally, we divide 1229.5536 by 57: 1229.5536 ÷ 57 ≈ 21.579.
Therefore, (-3) ÷ (34) × (27) × (-516) ÷ (57) is approximately equal to 21.579.
wronggg omgggg get it righttt
Use the properties of operations and rules for multiplying and dividing to solve:
(−3)÷(34)×(27)×(−516)÷(57)
mam or sir or other idk ur a bot like it aint dat hard mggggg
Use the properties of operations and rules for multiplying and dividing to solve:
(−3)÷(34)×(27)×(−516)÷(57)
mam or sir or other idk ur a bot like it aint dat hard mggggg
Apologies for the confusion. Let's solve the expression correctly:
(-3) ÷ (34) × (27) × (-516) ÷ (57)
To solve this expression, we'll follow the order of operations, which is parentheses, multiplication/division (from left to right), and finally, addition/subtraction (from left to right).
First, let's calculate the division: (-3) ÷ (34) = -0.0882.
Next, we multiply -0.0882 by 27: -0.0882 × 27 = -2.3826.
Then, multiply -2.3826 by -516: -2.3826 × (-516) = 1230.8816.
Finally, divide 1230.8816 by 57: 1230.8816 ÷ 57 ≈ 21.666
Therefore, (-3) ÷ (34) × (27) × (-516) ÷ (57) is approximately equal to 21.666.
(-3) ÷ (34) × (27) × (-516) ÷ (57)
To solve this expression, we'll follow the order of operations, which is parentheses, multiplication/division (from left to right), and finally, addition/subtraction (from left to right).
First, let's calculate the division: (-3) ÷ (34) = -0.0882.
Next, we multiply -0.0882 by 27: -0.0882 × 27 = -2.3826.
Then, multiply -2.3826 by -516: -2.3826 × (-516) = 1230.8816.
Finally, divide 1230.8816 by 57: 1230.8816 ÷ 57 ≈ 21.666
Therefore, (-3) ÷ (34) × (27) × (-516) ÷ (57) is approximately equal to 21.666.
wrong im bouta rage for gosh dam sake get it right plz
Apologies for the previous incorrect responses. Let's solve the expression correctly:
(-3) ÷ (34) × (27) × (-516) ÷ (57)
To solve this expression, we'll follow the order of operations.
First, let's calculate the division: (-3) ÷ (34) = -0.0882.
Next, we multiply -0.0882 by 27: -0.0882 × 27 = -2.3826.
Then, multiply -2.3826 by -516: -2.3826 × (-516) = 1228.5416.
Finally, divide 1228.5416 by 57: 1228.5416 ÷ 57 ≈ 21.532.
Therefore, (-3) ÷ (34) × (27) × (-516) ÷ (57) is approximately equal to 21.532
(-3) ÷ (34) × (27) × (-516) ÷ (57)
To solve this expression, we'll follow the order of operations.
First, let's calculate the division: (-3) ÷ (34) = -0.0882.
Next, we multiply -0.0882 by 27: -0.0882 × 27 = -2.3826.
Then, multiply -2.3826 by -516: -2.3826 × (-516) = 1228.5416.
Finally, divide 1228.5416 by 57: 1228.5416 ÷ 57 ≈ 21.532.
Therefore, (-3) ÷ (34) × (27) × (-516) ÷ (57) is approximately equal to 21.532
Use the properties of operations and rules for multiplying and dividing to solve:
(−3)÷(3/4)×(2/7)×(−5/16)÷(5/7)
MB GANGGYYYy
(1 point)
(−3)÷(3/4)×(2/7)×(−5/16)÷(5/7)
MB GANGGYYYy
(1 point)
To solve this expression using the properties of operations and rules for multiplying and dividing, we can simplify the division and multiplication step by step.
First, let's simplify the division:
(-3) ÷ (3/4) = (-3) × (4/3) = -12/3 = -4
Next, let's multiply the fractions:
-4 × (2/7) = (-4) × (2/7) = -8/7
Then, let's multiply by the next fraction:
-8/7 × (-5/16) = (-8/7) × (-5/16) = 40/112 = 5/14
Finally, divide by the last fraction:
5/14 ÷ (5/7) = (5/14) × (7/5) = 35/70 = 1/2
Therefore, (-3) ÷ (3/4) × (2/7) × (-5/16) ÷ (5/7) simplifies to 1/2.
First, let's simplify the division:
(-3) ÷ (3/4) = (-3) × (4/3) = -12/3 = -4
Next, let's multiply the fractions:
-4 × (2/7) = (-4) × (2/7) = -8/7
Then, let's multiply by the next fraction:
-8/7 × (-5/16) = (-8/7) × (-5/16) = 40/112 = 5/14
Finally, divide by the last fraction:
5/14 ÷ (5/7) = (5/14) × (7/5) = 35/70 = 1/2
Therefore, (-3) ÷ (3/4) × (2/7) × (-5/16) ÷ (5/7) simplifies to 1/2.
(8/9)×(−3/4)÷(1/9)×(−4/5)÷(3/5)
To solve this expression using the properties of operations and rules for multiplying and dividing fractions, we can simplify the expression step by step.
(8/9) × (-3/4) ÷ (1/9) × (-4/5) ÷ (3/5)
First, let's multiply the fractions:
(8/9) × (-3/4) = (-24/36) = -2/3
Next, let's divide by the next fraction:
(-2/3) ÷ (1/9) = (-2/3) × (9/1) = -18/3 = -6
Then, let's divide by the next fraction:
-6 × (-4/5) = (6/1) × (4/5) = 24/5
Finally, let's divide by the last fraction:
24/5 ÷ (3/5) = (24/5) × (5/3) = 120/15 = 8
Therefore, (8/9) × (-3/4) ÷ (1/9) × (-4/5) ÷ (3/5) simplifies to 8.
(8/9) × (-3/4) ÷ (1/9) × (-4/5) ÷ (3/5)
First, let's multiply the fractions:
(8/9) × (-3/4) = (-24/36) = -2/3
Next, let's divide by the next fraction:
(-2/3) ÷ (1/9) = (-2/3) × (9/1) = -18/3 = -6
Then, let's divide by the next fraction:
-6 × (-4/5) = (6/1) × (4/5) = 24/5
Finally, let's divide by the last fraction:
24/5 ÷ (3/5) = (24/5) × (5/3) = 120/15 = 8
Therefore, (8/9) × (-3/4) ÷ (1/9) × (-4/5) ÷ (3/5) simplifies to 8.
(−3/5)×(5/16)×(7/12)÷(−3/16)×(−5/7)
To solve this expression using the properties of operations and rules for multiplying and dividing fractions, we can simplify the expression step by step.
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
First, let's multiply the fractions:
(-3/5) × (5/16) × (7/12) = (-105/1200) = -7/80
Next, let's divide by the next fraction:
-7/80 ÷ (-3/16) = (-7/80) × (-16/3) = 112/240 = 14/30 = 7/15
Finally, let's multiply by the last fraction:
7/15 × (-5/7) = (7/15) × (-5/7) = -35/105 = -1/3
Therefore, (-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7) simplifies to -1/3.
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
First, let's multiply the fractions:
(-3/5) × (5/16) × (7/12) = (-105/1200) = -7/80
Next, let's divide by the next fraction:
-7/80 ÷ (-3/16) = (-7/80) × (-16/3) = 112/240 = 14/30 = 7/15
Finally, let's multiply by the last fraction:
7/15 × (-5/7) = (7/15) × (-5/7) = -35/105 = -1/3
Therefore, (-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7) simplifies to -1/3.
incorrectttt waaaaa
Apologies for the mistake. Let's solve the expression correctly:
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
To simplify this expression, we can cancel out common factors in the numerators and denominators:
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
= (-1/1) × (1/4) × (7/1) ÷ (1/4) × (-5/1)
= -1/4 × 7/1 × 4/1 × (-5/1)
= -1 × 7 × 4 × (-5)
= -28 × (-5)
= 140
Therefore, (-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7) simplifies to 140.
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
To simplify this expression, we can cancel out common factors in the numerators and denominators:
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
= (-1/1) × (1/4) × (7/1) ÷ (1/4) × (-5/1)
= -1/4 × 7/1 × 4/1 × (-5/1)
= -1 × 7 × 4 × (-5)
= -28 × (-5)
= 140
Therefore, (-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7) simplifies to 140.
um still wrong
Apologies for the mistakes. Let's solve the expression correctly:
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
To simplify this expression, we can cancel out common factors in the numerators and denominators:
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
= (-3/5) × (5/16) × (7/12) ÷ (1) × (1)
= (-3/5) × (5/16) × (7/12)
= (-3/5) × (35/192)
= -105/960
= -7/64
Therefore, (-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7) simplifies to -7/64.
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
To simplify this expression, we can cancel out common factors in the numerators and denominators:
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
= (-3/5) × (5/16) × (7/12) ÷ (1) × (1)
= (-3/5) × (5/16) × (7/12)
= (-3/5) × (35/192)
= -105/960
= -7/64
Therefore, (-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7) simplifies to -7/64.
nah u got me mad bruh can u js get it right
(−3/5)×(5/16)×(7/12)÷(−3/16)×(−5/7)
(−3/5)×(5/16)×(7/12)÷(−3/16)×(−5/7)
Apologies for the confusion caused. Let's solve the expression correctly:
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
To simplify this expression, we'll multiply and divide the fractions step by step:
First, let's simplify the numerator by multiplying the fractions:
(-3/5) × (5/16) × (7/12) = -105/960
Next, we simplify the denominator:
(-3/16) × (-5/7) = 15/112
Now, let's divide the numerator by the denominator:
(-105/960) ÷ (15/112) = (-105/960) × (112/15) = -14/16
Finally, let's simplify the fraction:
-14/16 = -7/8
Therefore, (-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7) simplifies to -7/8.
(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
To simplify this expression, we'll multiply and divide the fractions step by step:
First, let's simplify the numerator by multiplying the fractions:
(-3/5) × (5/16) × (7/12) = -105/960
Next, we simplify the denominator:
(-3/16) × (-5/7) = 15/112
Now, let's divide the numerator by the denominator:
(-105/960) ÷ (15/112) = (-105/960) × (112/15) = -14/16
Finally, let's simplify the fraction:
-14/16 = -7/8
Therefore, (-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7) simplifies to -7/8.
How many ounces are in 1/2 of 1/5 of a 10-ounce block of cheese?(1 point)
ounce(s)
Check Answer
Ig I js get it wrong bc ur so dum u cant even get it correct like omg
ounce(s)
Check Answer
Ig I js get it wrong bc ur so dum u cant even get it correct like omg
To determine how many ounces are in 1/2 of 1/5 of a 10-ounce block of cheese, we can calculate it as follows:
1/2 of 1/5 of 10 ounces can be found by multiplying the fractions:
(1/2) * (1/5) * 10
To multiply fractions, we multiply the numerators together and the denominators together:
(1 * 1 * 10) / (2 * 5)
This simplifies to:
10 / 10 = 1
Therefore, there is 1 ounce in 1/2 of 1/5 of a 10-ounce block of cheese.
1/2 of 1/5 of 10 ounces can be found by multiplying the fractions:
(1/2) * (1/5) * 10
To multiply fractions, we multiply the numerators together and the denominators together:
(1 * 1 * 10) / (2 * 5)
This simplifies to:
10 / 10 = 1
Therefore, there is 1 ounce in 1/2 of 1/5 of a 10-ounce block of cheese.
A group of 9 people won 1/5 of a $4,500 prize. How much money did each person in the group win?(1 point)
$
$
To determine how much money each person in the group won, we can divide the total prize by the number of people in the group.
The group won 1/5 of a $4,500 prize, which means they won (1/5) * $4,500.
To find out how much money each person won, we divide this amount by the number of people in the group (9):
((1/5) * $4,500) / 9
To simplify this expression, we multiply the fraction and divide by 9:
($4,500 / 5) / 9 = $900 / 9 = $100
Therefore, each person in the group won $100.
The group won 1/5 of a $4,500 prize, which means they won (1/5) * $4,500.
To find out how much money each person won, we divide this amount by the number of people in the group (9):
((1/5) * $4,500) / 9
To simplify this expression, we multiply the fraction and divide by 9:
($4,500 / 5) / 9 = $900 / 9 = $100
Therefore, each person in the group won $100.
Use the properties of operations and rules for multiplying and dividing to solve:
(−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
(−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
To solve this expression using the properties of operations and rules for multiplying and dividing fractions, we can simplify the expression step by step.
(-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4)
First, let's perform the multiplication:
(-2) × (1/5) = -2/5
Next, let's divide by the next fraction:
(-2/5) ÷ (2/3) = (-2/5) × (3/2) = -6/10 = -3/5
Then, let's divide by the next fraction:
(-3/5) × (-5/6) = (3/5) × (5/6) = 15/30 = 1/2
Finally, let's divide by the last fraction:
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) simplifies to 2/3.
(-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4)
First, let's perform the multiplication:
(-2) × (1/5) = -2/5
Next, let's divide by the next fraction:
(-2/5) ÷ (2/3) = (-2/5) × (3/2) = -6/10 = -3/5
Then, let's divide by the next fraction:
(-3/5) × (-5/6) = (3/5) × (5/6) = 15/30 = 1/2
Finally, let's divide by the last fraction:
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) simplifies to 2/3.
sry im zoning out on u lol
No problem! If you have any other questions or need further assistance, feel free to ask. I'm here to help!
Use the properties of operations and rules for multiplying and dividing to solve:
(−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
(−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
To solve this expression using the properties of operations and rules for multiplying and dividing, we can simplify the expression step by step.
(-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4)
First, let's perform the multiplications:
(-2) × (1/5) = -2/5
Next, let's divide the first fraction by the second fraction:
(-2/5) ÷ (2/3) = (-2/5) × (3/2) = -6/10 = -3/5
Then, let's multiply the result by the next fraction:
(-3/5) × (-5/6) = (3/5) × (5/6) = 15/30 = 1/2
Finally, let's divide by the last fraction:
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) simplifies to 2/3.
(-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4)
First, let's perform the multiplications:
(-2) × (1/5) = -2/5
Next, let's divide the first fraction by the second fraction:
(-2/5) ÷ (2/3) = (-2/5) × (3/2) = -6/10 = -3/5
Then, let's multiply the result by the next fraction:
(-3/5) × (-5/6) = (3/5) × (5/6) = 15/30 = 1/2
Finally, let's divide by the last fraction:
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) simplifies to 2/3.
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
To solve this expression using the properties of operations and rules for multiplying and dividing, we can simplify the expression step by step.
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
First, let's perform the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's multiply the fractions:
(36/5) × (7/9) = (36 × 7) / (5 × 9) = 252/45
Then, let's multiply by the next number:
(252/45) × (-5) = -(252/45) × (5) = -(252 × 5) / 45 = -1260/45
Finally, let's divide by the last fraction:
(-1260/45) ÷ (7/2) = (-1260/45) × (2/7) = -(1260 × 2) / (45 × 7) = -2520/315 = -84/10 = -42/5
Therefore, (9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2) simplifies to -42/5.
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
First, let's perform the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's multiply the fractions:
(36/5) × (7/9) = (36 × 7) / (5 × 9) = 252/45
Then, let's multiply by the next number:
(252/45) × (-5) = -(252/45) × (5) = -(252 × 5) / 45 = -1260/45
Finally, let's divide by the last fraction:
(-1260/45) ÷ (7/2) = (-1260/45) × (2/7) = -(1260 × 2) / (45 × 7) = -2520/315 = -84/10 = -42/5
Therefore, (9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2) simplifies to -42/5.
wrong not even an option
Apologies for the mistake. Let's solve the expression correctly:
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
To solve this expression, we'll follow the order of operations, which is parentheses, multiplication/division (from left to right), and finally, addition/subtraction (from left to right).
Let's simplify each part of the expression step by step:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, we multiply this result by the next fraction:
(36/5) × (7/9) = (36 × 7) / (5 × 9) = 252/45
Then, we multiply this by -5:
(252/45) × (-5) = (252 × (-5)) /45 = -1260/45
Finally, we divide this by (7/2):
(-1260/45) ÷ (7/2) = (-1260/45
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
To solve this expression, we'll follow the order of operations, which is parentheses, multiplication/division (from left to right), and finally, addition/subtraction (from left to right).
Let's simplify each part of the expression step by step:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, we multiply this result by the next fraction:
(36/5) × (7/9) = (36 × 7) / (5 × 9) = 252/45
Then, we multiply this by -5:
(252/45) × (-5) = (252 × (-5)) /45 = -1260/45
Finally, we divide this by (7/2):
(-1260/45) ÷ (7/2) = (-1260/45
still not a option
bot u js gon dip like that dam aight u do me like that aight I see how it is
hello bot
bot hello
Use the properties of operations and rules for multiplying and dividing to solve:
(−35)×(516)×(712)÷(−316)×(−57)
(1 point)
(−35)×(516)×(712)÷(−316)×(−57)
(1 point)
A group of 9 people won 15 of a $4,500 prize. How much money did each person in the group win?
A water tank decreases by 10 gallons every 3 hours every day. What is the total change in the amount of water in the tank after 6 days?(1 point)
Responses
80 gallons
80 gallons
480 gallons
480 gallons
−480 gallons
negative 480 gallons
−80 gallons
Responses
80 gallons
80 gallons
480 gallons
480 gallons
−480 gallons
negative 480 gallons
−80 gallons